The Effect of Pictorial Models Health Education on Mother Skill in Determining Early Anemia on Primary School Children - Aniharyati Aniharyati; Haris Haris; Ahmad Ahmad (Universitas Muhammadiyah Semarang, 2018)
Introduction: Early detection of anemia can be performed by mother and the mother should have knowledge and skills in it. Health education is a strategy in providing knowledge, comprehension, abilities and skills for empowerment. This is a quasi-experimental research with pre and post-test design in the same group. Researchers will assess mothers who have elementary school children before and after a pictorial model health education given on how to detect early anemia in primary school children. This research was conducted in Bontokape Village, Bolo Sub-district, Bima Regency. The population of this research was 150 people and 60 people were chosen as samples by purposive sampling technique. Data were analyzed by Wilcoxon test. Results: Unskilled category respondents are 91,7% before health education given and decrease to 0% after health education.Pictorial model health education is significantly influence on early detection mother skill of anemia in primary school children (p-value 0,00). Discussion: Narration and animation in teaching and learning process is an interesting media and proven effectively to improve learning result. Pictorial model health education can significantly improve the mother's skills.